IMF Survey, Volume 36 Issue 11. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2007)
IMF plan to cut imbalances; IMF clarifies aid role; world growth update; financial globalization; growth in Africa; low-income countries need fiscal reform; Central America seeks stronger growth; IMF surveillance framework; news briefs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet